A Pilot Study Describing Access to Emergency Care in Two States Using a Model Emergency Care Categorization System. (16th September 2013) - Myers, Sage R.; Salhi, Rama A.; Lerner, E. Brooke; Gilson, Rebecca; Kraus, Andrea; Kelly, John J.; Hargarten, Stephen; Carr, Brendan G.
Abstract: Objectives: The Institute of Medicine (IOM)'s "Future of Emergency Care" report recommended the categorization and regionalization of emergency care, but no uniform system to categorize hospital emergency care capabilities has been developed. The absence of such a system limits the ability to benchmark outcomes, to develop regional systems of care, and of patients to make informed decisions when seeking emergency care. The authors sought to pilot the deployment of an emergency care categorization system in two states. Methods: A five‐tiered emergency department (ED) categorization system was designed, and a survey of all Pennsylvania and Wisconsin EDs was conducted. This 46‐item survey described hospital staffing, characteristics, resources, and practice patterns. Based on responses, EDs were categorized as limited, basic, advanced, comprehensive, and pediatric critical care capable. Prehospital transport times were then used to determine population access to each level of care. Results: A total of 247 surveys were received from the two states (247 of 297, 83%). Of the facilities surveyed, roughly one‐quarter of hospitals provided advanced care, 10.5% provided comprehensive care, and 1.6% provided pediatric critical care. Overall, 75.1% of the general population could reach an advanced or comprehensive ED within 60 minutes by ground transportation. Among the pediatric population (age 14 years and younger), 56.2% could reach a pediatric critical care or comprehensive ED, with another 19.5% being able to access an advanced ED within 60 minutes. Conclusions: Using this categorization system, fewer than half of all EDs provide advanced or comprehensive emergency care. While the majority of the population has access to advanced or comprehensive care within an hour, a significant portion (25%) does not. This article describes how an ED categorization scheme could be developed and deployed across the United States. There are implications for prehospital planning, patient decision‐making, outcomes measurement, interfacility transfer coordination, and development of regional emergency care systems.